2018
DOI: 10.1161/jaha.117.008202
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Specific Associations Between Alcohol Consumption and Incidence of Hypertension: A Systematic Review and Meta‐Analysis of Cohort Studies

Abstract: BackgroundAlthough it is well established that heavy alcohol consumption increases the risk of hypertension, the risk associated with low levels of alcohol intake in men and women is unclear.Methods and ResultsWe searched Medline and Embase for original cohort studies on the association between average alcohol consumption and incidence of hypertension in people without hypertension. Random‐effects meta‐analyses and metaregressions were conducted. Data from 20 articles with 361 254 participants (125 907 men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
5
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 73 publications
8
102
5
4
Order By: Relevance
“…They found that frequency of binge drinking was associated with elevated levels of systolic blood pressure in men but not women. This result is in some ways supported by the work of Roerecke et al,2 who similarly found a less pronounced effect of average alcohol intake on risk of developing hypertension in women. However, this study regrettably falls short of “completing the puzzle” of whether this difference in association with blood pressure by sex is driven by variation in drinking pattern (ie, episodes of heavy drinking being more common in men) through having not included either adjustment for, or the formal testing of an interaction with, overall volume of alcohol consumed.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…They found that frequency of binge drinking was associated with elevated levels of systolic blood pressure in men but not women. This result is in some ways supported by the work of Roerecke et al,2 who similarly found a less pronounced effect of average alcohol intake on risk of developing hypertension in women. However, this study regrettably falls short of “completing the puzzle” of whether this difference in association with blood pressure by sex is driven by variation in drinking pattern (ie, episodes of heavy drinking being more common in men) through having not included either adjustment for, or the formal testing of an interaction with, overall volume of alcohol consumed.…”
Section: Introductionsupporting
confidence: 70%
“…Roerecke and colleagues2 carried out a systematic review and dose–response meta‐analysis of the association between alcohol consumption, defined using average number of drinks consumed per day, and incident hypertension separately in men and women. They found that no level of alcohol intake was associated with a lower risk of developing hypertension in either sex, which is in contrast to previous systematic reviews of this topic as well as observational studies of alcohol consumption and some cardiovascular outcomes 3, 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no threshold level below which alcohol consumption exerted a beneficial effect on the development of hypertension both in Asian and Western men. Our data, along with a recent meta-analysis [21], could serve as additional evidence in establishing the recommendations in each region.…”
Section: Discussionmentioning
confidence: 75%
“…As an example, one can consider the relationship between alcohol and the risk of hypertension where 1 drink per day on average has been shown to increase blood pressure and the risk of hypertension (Roerecke et al., ). Consider a patient with hypertension and alcohol consumption: There is a good chance that her or his hypertension has been caused or worsened by alcohol consumption, fulfilling the definition of “harmful drinking.” But is such a diagnosis clinically meaningful when we cannot draw a definitive link?…”
Section: Is It Likely That the Icd‐11 And Its Criteria Will Actually mentioning
confidence: 99%